2011
DOI: 10.1117/12.879507
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometer characterization of reactions in photoresists exposed to extreme ultraviolet radiation

Abstract: The development of resists that meet the requirements for resolution, line edge roughness and sensitivity remains one of the challenges for extreme ultraviolet (EUV) lithography. Two important processes that contribute to the lithographic performance of EUV resists involve the efficient decomposition of a photoacid generator (PAG) to yield a catalytic acid and the subsequent deprotection of the polymer in the resist film. We investigate these processes by monitoring the trends produced by specific masses outga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…IMEC determined outgassing rates in the m/z ¼ 45-200 range under an irradiance of 10 mW cm À2 , 7-10 whereas CNSE/SEMATECH counted them in the m/z ¼ 35-200 range (excluding 44) under an irradiance of 15 mW cm À2 . [17][18][19][20] The deviation of assessing outgassing rates with different irradiances can be calculated according to the first-order integrated rate law as (1 -exp(-Dill's C parameter  irradiance)]/irradiance, where Dill's C parameter was approximated 4  10 À3 mJ À1 cm 2 from our previous CH 3 þ outgassing results. 28 The outgassing rates determined with an actual irradiance of 10 or 15 mW cm À2 differed by approximately 6% or 5%, respectively, from the results obtained with an actual irradiance of 38 mW cm À2 and scaled to a value of either 10 or 15 mW cm À2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…IMEC determined outgassing rates in the m/z ¼ 45-200 range under an irradiance of 10 mW cm À2 , 7-10 whereas CNSE/SEMATECH counted them in the m/z ¼ 35-200 range (excluding 44) under an irradiance of 15 mW cm À2 . [17][18][19][20] The deviation of assessing outgassing rates with different irradiances can be calculated according to the first-order integrated rate law as (1 -exp(-Dill's C parameter  irradiance)]/irradiance, where Dill's C parameter was approximated 4  10 À3 mJ À1 cm 2 from our previous CH 3 þ outgassing results. 28 The outgassing rates determined with an actual irradiance of 10 or 15 mW cm À2 differed by approximately 6% or 5%, respectively, from the results obtained with an actual irradiance of 38 mW cm À2 and scaled to a value of either 10 or 15 mW cm À2 .…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the development of the witness-plate method, new EUV photosensitive samples had to pass certain preset outgassing criteria before they could be exposed under an EUV exposure tool. [7][8][9][10][16][17][18][19][20][21][22][23][24][25][26] Although the characterization of outgassed species and the quantification of outgassing are no longer used for resist a) Author to whom correspondence should be addressed; electronic mail: graceho@nuk.edu.tw qualification by the majority of the EUVL community, these techniques can provide useful information for understanding the photochemical mechanisms of outgassing, which can help in the design of new photosensitive materials. Semiconductor Manufacturing Technology (SEMATECH) organized a roundrobin resist test to measure the absolute outgassing rates from an EUV model photoresist at eight measurement sites and reported that the absolute values varied over 4 orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The oxalate ligand will decompose readily when detached from the metal center and produce carbon dioxide in the process. The rate of CO2 production can be monitored using in situ mass spectrometry measurements [29][30][31][32] . [24][25][26][27][28] .…”
Section: Cr2+mentioning
confidence: 99%